Health Examination And Hypertension Gymnastics For Older Adults At Bina Bhakti Foundation Babakan Setu, Tangerang - Yakobus Siswadi; Masrida Adolina Panjaitan; Marianna T; Bima A. S; Elissa O. H (Universitas Malahayati Lampung, 2022)
ABSTRACT Background: Older adults are those entering the age of 60. Life expectancy among elderly has been a valuable indicator for the overall health of inhabitant. Older adults commonly experience a decline in health, due to aging or diseases. Several programs to increase the life expectancy of elderly population are hence of urgency. The direct survey revealed that there are 100 older adults in Bina Bhakti foundation, of which 66 people are able to walk and use wheelchairs, while 34 people are on complete bed rest. Furthermore, many of them had chronic diseases such as joint disease, hypertension, and heart disease. The Management of Bina Bhakti Foundation conducts periodic health examination once a month for those who are on total bed rest, and once a year for those who are still physically active. It is all carried out by nurses and general practitioners at the Bina Bhakti Foundation. Objective: This community service aims to provide hypertension education and gymnastics with the theme of “being healthy and independent elderly”. Method: The target is all elderly people being detected to have an increase in blood pressure. The program encompasses lecturing session, health screening, and hypertension gymnastics. Screening test of glucose, cholesterol, and blood pressure was conducted at the end of program. To ensure that each process went well, the team held discussion, practice and assistance to the elderly during gymnastics. Result: In a nutshell, all activities under this program went well. As many as 66 elderly people underwent health checks which included blood pressure, blood sugar, and cholesterol. It was found that among 66 respondents, 19 elderly had increased blood pressure,1 person had an increased in blood sugar and 13 people had a high cholesterol without high blood pressure from 66 respondents. Conclusion: The survey showed that many older adults in Bina Bhakti were diagnosed with hypertension, joint disease, heart disease, and diabetes mellitus. Respondents and nurses of the Bina Bhakti Foundation said that this educational activity and hypertension gymnastic were the first at Bina Bhakti Foundation. We expected that the program could be carried out with different topics about the effect of self-acupressure on reducing blood pressure. Keywords: Older adults, Hypertension education, Hypertension Gymnastics